Pulmonary Blastomycosis: A Case from Africa. (2008) - Cheikh Rouhou, Sana; Racil, Hajer; Ismail, Olfa; Trabelsi, Sonia; Zarrouk, Mourad; Chaouch, Nawel; Hantous, Sawssen; Khaled, Samira; El Mezni, Faouzi; Chabbou, Abdellatif
Abstract : Pulmonary blastomycosis is an uncommon pathologic condition that is quite rare in Africa compared to endemic regions of Canada and the upper Midwest of the U.S. We describe a 45-year-old patient who complained of productive cough, hemoptysis, and dorsal rachiodynia. Chest imaging revealed a necrotic tissue-density pulmonary mass involving both the upper and lower right lobes. Chest MRI showed signal abnormality of the third thoracic vertebral body and the greater trochanter, consistent with metastatic lesions. Clinical and radiological findings were strongly suggestive of lung cancer. Diagnosis of pulmonary blastomycosis was made by visualization of yeast in bronchial biopsies and further confirmed by culture of bronchoalveolar lavage specimens. The patient was treated with itraconazole and his clinical condition improved markedly. Pulmonary blastomycosis is unusual in Africa and that fact caused a considerable delay in diagnosis. We suggest that this disease may be more common in Africa than has been previously suspected.